Algoritmos evolutivos híbridos aplicados no sequenciamento de produção em uma indústria de alimentos - Pereira Junior, Geraldo (2018)
This paper describes a comparative study of some production-scheduling scenarios for a real case in a food company located in Marilia, SP. For this problem, well known Job-Shop Scheduling Problem (JSSP), it was used two types of evolutionary algorithms: Genetic Algorithm and Differential Evolution. In order to increase the efficiency during the search process, these two algorithms have been adapted with local search techniques. Furthermore, it was proposed a heuristic based on load balancing in order to achieve promising regions in the search space. Finally, the proposed approaches have been validated for a real scenario from a food company.